1997
DOI: 10.1007/bf02803901
|View full text |Cite
|
Sign up to set email alerts
|

Ileal carbohydrates inhibit cholinergically stimulated exocrine pancreatic secretion in humans

Abstract: Exogenously stimulated pancreatic enzyme secretion was significantly inhibited by additional ileal carbohydrate perfusion (p < 0.05), whereas ileal saline had no effect. Moreover, plasma levels of GLP-1 increased significantly (p = 0.004) after ileal perfusion of carbohydrates, but not after saline. PYY plasma concentrations remained unchanged after both ileal perfusates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 37 publications
0
17
0
1
Order By: Relevance
“…It was first noted that GLP-1 inhibits gastrin-induced acid secretion in humans (261), and subsequently demonstrated that GLP-1 also inhibits meal-induced secretion as well as gastric emptying and pancreatic secretion (327). The effect on pancreatic exocrine secretion was first suspected to be secondary to the inhibition of gastric emptying, but in subsequent studies, GLP-1 was demonstrated to also inhibit pancreatic secretion in response to intraduodenal stimulation (84). The inhibitory effect of GLP-1 on acid secretion could be elicited by physiological elevations of the GLP-1 concentrations in plasma and was, remarkably, additive to the inhibitory effects of PYY, which is released from the L-cell in parallel with GLP-1 (324).…”
Section: E Effects On the Gastrointestinal Tractmentioning
confidence: 99%
“…It was first noted that GLP-1 inhibits gastrin-induced acid secretion in humans (261), and subsequently demonstrated that GLP-1 also inhibits meal-induced secretion as well as gastric emptying and pancreatic secretion (327). The effect on pancreatic exocrine secretion was first suspected to be secondary to the inhibition of gastric emptying, but in subsequent studies, GLP-1 was demonstrated to also inhibit pancreatic secretion in response to intraduodenal stimulation (84). The inhibitory effect of GLP-1 on acid secretion could be elicited by physiological elevations of the GLP-1 concentrations in plasma and was, remarkably, additive to the inhibitory effects of PYY, which is released from the L-cell in parallel with GLP-1 (324).…”
Section: E Effects On the Gastrointestinal Tractmentioning
confidence: 99%
“…PYY is secreted predominantly from endocrine cells in the ileum and colon and PP from endocrine cells in the pancreas, both in response to all three macronutrients, fat, carbohydrate, and protein, with fat being the most potent stimulus and carbohydrate the least potent or, possibly, impotent (2,16,29,33). Enteral administration of free fatty acids, including dodecanoate (3) or oleate (22), are known to be potent stimuli of PYY secretion.…”
mentioning
confidence: 99%
“…Previous experiment suggested a similar response to carbohydrates as administration of isotonic solutions of starch and maltose significantly inhibited pancreatic enzyme output stimulated with an intravenous infusion of the cholinergic agonist carbachol (Groger et al 1997) or by duodenal perfusion with a mixture of essential amino acids (450 μmol/min) (Layer et al 1990). Inhibitory effects of various enteral diets on the exocrine pancreatic secretion were demonstrated also in other reports using feeding tubes placed 10 cm or more distal to the ligament of Treitz (Pfeiffer et al 1993;Vidon et al 1988;Vu et al 1999).…”
Section: Applications To Other Conditionsmentioning
confidence: 95%